Conditional Oscillation of Half-Linear Differential Equations with Coefficients Having Mean Values. (7th July 2014) - Hasil, Petr; Mařík, Robert; Veselý, Michal
Abstract : We prove that the existence of the mean values of coefficients is sufficient for second-order half-linear Euler-type differential equations to be conditionally oscillatory. We explicitly find an oscillation constant even for the considered equations whose coefficients can change sign. Our results cover known results concerning periodic and almost periodic positive coefficients and extend them to larger classes of equations. We give examples and corollaries which illustrate cases that our results solve. We also mention an application of the presented results in the theory of partial differential equations.